2021
DOI: 10.18231/j.jpbs.2020.012
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine induced leukopenia: A case series

Abstract: This is a case series of 4 patients who developed leukopenia on, controlled-release carbamazepine (CBZ-CR) monotherapy for focal seizure prophylaxis. All 4 cases (2 males and 2 females), presented to the neurology department with history of episodes of sudden onset, abnormal body movements. Patients were diagnosed as cases of focal seizures and were prescribed tablet CBZ-CR 300 mg twice a day for seizure prophylaxis. One month later patients presented for follow-up and were continuing with the treatment. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…3 However, the decrease in TLC was transient and this recovered gradually at 3-months follow-up on continuing the treatment. 11 Study by Consoli D. et al, 18 reported that 1 out of 54 patients in CBZ group developed leukopenia.…”
Section: Hematological Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, the decrease in TLC was transient and this recovered gradually at 3-months follow-up on continuing the treatment. 11 Study by Consoli D. et al, 18 reported that 1 out of 54 patients in CBZ group developed leukopenia.…”
Section: Hematological Side Effectsmentioning
confidence: 99%
“…In CBZ-CR group 4 patients developed leukopenia, which was transient and reversed on continuing the treatment. 11 Table 1 shows the TLC levels observed in two groups.…”
Section: Adverse Eventsmentioning
confidence: 99%